La protection du château de Versailles durant la Première Guerre mondiale - Fiona Revello (Bulletin du Centre de Recherche du Château de Versailles)
If the signing of the peace treaty in the Hall of Mirrors, on 28 June 1919, makes the First World War a landmark in the history of the Palace of Versailles, the conflict itself plays a much less prominent part in the historiography of Versailles. Following a chronological approach, this article aims to retrace the preservation methods of the estate and its collections during the four years of combat. Going beyond the spatio-temporal boundaries of the Palace of Versailles and of the Great War, its reasoning is based on a two-pronged comparative assessment. On the one hand, it seeks to situate the Versailles experience of the First World War within the safeguarding policy of the national museums and palaces, that of the Louvre and of Fontainebleau in particular. On the other hand, it seeks to shed light on the period of the First World War in the context of the precedent set by the Franco-Prussian War, and to examine its impact on the Second World War. From this comparative overview, two main elements emerge: the hasty implementation of protection measures, despite the precedent experienced four decades earlier and in contrast with the anticipation characterizing the Second World War; and the tiny proportion of artworks evacuated by the Palace of Versailles, in contrast with the experience of the other national museums and palaces.